1987
DOI: 10.1159/000215570
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Monitoring of a Low Molecular Weight Heparin (Enoxaparin) with a New Clotting Test (Heptest)

Abstract: A new simple clotting test (Heptest) for low molecular weight heparins was compared to anti-Xa determination by an amidolytic assay in volunteers and in patients receiving standard calcium heparin or low molecular weight (LMW) heparin (Enoxaparin) by subcutaneous administration. The results obtained with both methods are in very good agreement. It seems that the Heptest, although influenced by various other clotting parameters, is nevertheless relatively specific for anti-Xa activity. Despite our positive firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 4 publications
2
14
0
3
Order By: Relevance
“…As unfrac tionated heparin, LMW heparins are mea sured with the anti-thrombin and anti-factor Xa tests. In those cases one observes that the anti-factor Xa test is more sensitive for LMW heparins than anti-thrombin tests [15][16][17], and that the sensitivity for one LMW heparin is different from another one [ 17], A relatively new test is the so-called heptest [18][19][20][21][22], In this test factor Xa is added to plasma and the clotting time is recorded. This test resembles the APTT, which up to now is the best assay for heparins.…”
Section: Introductionmentioning
confidence: 99%
“…As unfrac tionated heparin, LMW heparins are mea sured with the anti-thrombin and anti-factor Xa tests. In those cases one observes that the anti-factor Xa test is more sensitive for LMW heparins than anti-thrombin tests [15][16][17], and that the sensitivity for one LMW heparin is different from another one [ 17], A relatively new test is the so-called heptest [18][19][20][21][22], In this test factor Xa is added to plasma and the clotting time is recorded. This test resembles the APTT, which up to now is the best assay for heparins.…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐Xa activity measurement has been the most widely used method for assessing LMWHs activity and to establish a therapeutic range for a particular LMWH. Even if anti‐Xa and anti‐IIa activities have been well correlated with the dose of subcutaneous (s.c.) injection of LMWH (Hirsh et al , 1987; Frydman et al , 1988; Bara et al , 1987, 1990), experimental studies in animals have not demonstrated a strong correlation between antithrombotic activity and ex vivo anti‐Xa plasma levels (Holmer et al , 1982; Buchanan et al , 1985; Carter et al , 1982; Ockelford et al , 1982a; Fernandez et al , 1986). In contrast, some studies have found a significant statistical relationship between anti‐Xa plasma levels and both thrombotic and haemorrhagic outcomes with different LMWHs (Levine et al , 1989; Koller et al , 1986).…”
mentioning
confidence: 99%
“…The HEPTEST (Haemachem, St Louis, MO, USA) is a recently introduced clotting assay for anti-Xa activity which can be performed on automated coagulometers (Yin 1985). Good correlations between CS anti-Xa and the HEPTEST assays have been documented using both unfractionated and low molecular weight heparins (Baa et al 1987;Havenberg et al 1989). Use of the HEPTEST in pregnancy has not been validated.…”
Section: Introductionmentioning
confidence: 99%